Lipper's rating and the performance of unit trusts in Malaysia - Abdullah, A.R.; Abdullah, N.A.H. (Emerald Group Publishing Limited, 2015)
Purpose – The purpose of this paper is to examine the risk-adjusted performance of rated funds and determine the usefulness of Lipper Leader rating of unit trusts in Malaysia during the period 2000 to 2010. Design/methodology/approach – The paper utilizes the Sharpe ratio, Treynor ratio, Jensen’s alpha and Fama-French three-factor model to measure performance. Findings – During the period of study, the performance of the market index and risk-free rate outperformed that of 68 equity unit trust funds in the 3-year, 5-year and 10-year investment horizons. The ranking, based on four performance measures, corresponds to Lipper rating for the lowest rated and leader funds, but not for the three- and four-key rated funds. Further, there is a significant difference in the performance of the five-key, four-key and three-key rated funds which outperform the lowest rated funds, indicating that Lipper rating is able to distinguish superior and inferior unit trust funds. Research limitations/implications – Some of the limitations in this study are that the indexes could be self-constructed. The existing index might not represent the asset allocation of the funds concerned. Additional variables might have to be considered when examining fund performance as they should correspond to the characteristics of a fund. Practical implications – The results indicate that Lipper rating classification could identify the highest and lowest performing funds. Therefore, investors could use this rating to make informed investment decisions without undertaking time-consuming analysis to ascertain the good- and bad-quality funds in the market. Social implications – The findings of this study could be used by the academia as another source of reference to enhance their understanding of the applicability of Lipper rating for unit trust funds in an emerging market. Originality/value – The contribution of this study is that it analyzes the effectiveness and capability of Lipper Leader rating in identifying quality funds in the context of an emerging market. Performance comparison between Lipper Leader rating and methods used in the portfolio theory bridges the theory-practice gap between practitioners and academics. To date, there have been no attempts to study and compare the ratings of advisory firms with theoretical performance measures, particularly in the context of Malaysia